Induction of apoptosis in human colorectal cancer cells by nanovesicles from fingerroot (Boesenbergia rotunda (L.) Mansf.) - Saharut Wongkaewkhiaw (2022)
Colorectal cancer is the leading cause of cancer-related deaths worldwide, warranting the urgent need for a new treatment option. Plant-derived nanovesicles containing bioactive compounds represent new therapeutic avenues due to their unique characteristics as natural nanocarriers for bioactive molecules with therapeutic effects. Recent evidence has revealed potential anticancer activity of bioactive compounds from Boesenbergia rotunda (L.) Mansf. (fingerroot). However, the effect and the underlying mechanisms of fingerroot-derived nanovesicles (FDNVs) against colorectal cancer are still unknown. We isolated the nanovesicles from fingerroot and demonstrated their anticancer activity against two colorectal cancer cell lines, HT-29 and HCT116. The IC50 values were 63.9 ± 2.4, 57.8 ± 4.1, 47.8 ± 7.6 μg/ml for HT-29 cells and 57.7 ± 6.6, 47.2 ± 5.2, 34 ± 2.9 μg/ml for HCT116 cells at 24, 48, and 72 h, respectively. Interestingly, FDNVs were not toxic to a normal colon epithelial cell line, CCD 841 CoN. FDNVs exhibited selective uptake by the colorectal cancer cell lines but not the normal colon epithelial cell line. Moreover, dose- and time-dependent FDNV-induced apoptosis was only observed in the colorectal cancer cell lines. In addition, reactive oxygen species levels were substantially increased in colorectal cancer cells, but total glutathione decreased after treatment with FDNVs. Our results show that FDNVs exhibited selective anticancer activity in colorectal cancer cell lines via the disruption of intracellular redox homeostasis and induction of apoptosis, suggesting the utility of FDNVs as a novel intervention for colorectal cancer patients.